New Drainage Records and Revised Ranges for Sympatric Pirate Perch Species in Alabama, Florida, and Georgia - Tyler Muller; Bryson Hilburn; Lily Hughes (Southeastern Fishes Council Proceedings, 2025)
We report updated ranges for four sympatric species of Pirate Perches following a recent taxonomic revision of Aphredoderus. Using observations from recent sampling by the North Carolina State Museum of Natural Sciences and reidentifying cataloged specimens from the Georgia Museum of Natural History and Auburn University Museum collections, we were able to refine the distributions of four species throughout a complicated sympatric zone spanning coastal plain drainages in Alabama, Florida, and Georgia. We find that A. gibbosus is present in low numbers in the Flint, Escambia, Choctawhatchee, and Chattahoochee basins. These additional records nearly link the previously reported disjunct distribution of A. gibbosus into a more continuous distribution, though it still appears to be rare in this part of its range. We identified A. ornatus in Patsiliga Creek (Flint basin), and A. mesotrema in basins between the Mobile River and the Escambia River, and in the Alabama River. Following field observations that A. retrodorsalis is only present at low elevations, we narrow the range this species to being generally below 65 meters elevation in basins from the Blackwater River in Florida to the Ogeechee River in Georgia. This pattern contrasts with the sympatric species A. ornatus, which extends to (and at times past) the Atlantic Coastal Plain fall line in Georgia.
Keywords: Biogeography; Aphredoderus; Percopsiformes